Quality differences and profiling of volatile components between fermented and unfermented cocoa seeds (Theobroma cacao L.) of Criollo, Forastero and Trinitario in China - Dewei Yang; Baoduo Wu; Xiaowei Qin; Xiu Zhao; Zihui Zhu; Lin Yan; Fenju Zhang; Guoxing Wu; Fupeng Li (Beverage Plant Research)
Fermentation plays a crucial role and contributes to the quality of cocoa beans, the basis of chocolate products. The aim of this study was to evaluate the levels of chemical and aromatic compounds in the cocoa beans of Criollo, Forastero and Trinitario in China. Besides fermentation, unfermented beans of the three genetic groups were also analyzed. The results indicated that genotype involvement played an important role, contributing to cocoa volatile profiling and quality traits. The three cocoa groups' mass indicators all demonstrated some degree of decline after fermentation. After HS-SPME-GC-MS testing, 48 compounds were found in raw beans and 79 compounds in fermented beans. Trinitario contained the most volatile compounds with the highest levels of alcohol, while Criollo contained the highest ester content in unfermented beans. Alcohols and esters were characteristic components of Criollo fermented beans with 37.33% and 14.81%, respectively. The content of acetic acid was as high as 50% in the fermented beans of Forastero and Trinitario and only 35.42% in Criollo. The feature compounds of Criollo fermented beans showed an aromatic profile related to flower flavor, fruit flavor, green flavor, baking flavor and nut flavor. While the characteristic volatile compounds were mainly associated with descriptors of sour, buttery, fruity, roasted and nutty notes for Forastero and Trinitario fermented beans. The results of this study revealed the characteristics of three genetic groups of cocoa beans that will ultimately contribute to the breeding of excellent aroma varieties and cocoa production sustainability in Hainan Province, China.